The inorganic chemicals that surround us: role of tellurium, selenium and zinc on behavioural functions in mammals - Alvarez, Edgardo Oscar (2021)
Living organisms live in continuous interaction with its environment.During this process changes in one can induce adaptive responses on theother. Many factors in the environment have been studied with thenotorious distinction of been rare or to be of high intensity strength in itsinteraction with living organisms. However, little attention has been puton some factors that have constant interaction with organisms butusually have low intensity strength, such as the case of the inorganicchemical environment that surrounds us. In this review, the interactionbetween the chemical element and living organisms is discussed under atheoretical model of interaction between compartments, giving attentionto tellurium (Te), zinc (Zn) and selenium (Se) on some cognitivefunctions in human and animals. After studies in our laboratory of thephenotypic expression of the HSR (Hand Skill Relative) gene in schoolchildren community living in geographic zone rich in minerals andmines of La Rioja province, Argentine, where Te was found to be inhigher non‐toxic concentrations, a translational experimental model tomaturing rats exposed to this trace element was made. Te was found toincrease some parameters related to locomotion in an open field inducedby novelty and exploratory motivation. At the same time, inhibition oflateralized responses, survival responses and social activity was alsoobserved. Some of these changes, particularly those related tolateralization had similarity with that found previously in children of LaRioja province. Discussion of similarities and discrepancies of biologiceffects between animals and humans, about the possible meaning of Teand its interaction with Zn and Se with relevance to humans wasanalyzed.